Effect of nitrogen fertilizer to the flavonoid content of red amaranth (Amaranthus gangeticus L.) - Pratiwi, Ambar (Universitas Ahmad Dahlan, 2017)
ABSTRACT Red amaranth (Amaranthus gangeticus L.) is a vegetable that has been frequently consumed. The red color in red spinach leaves due to the anthocyanin that is included in the flavonoid compounds. Flavonoid compounds are very usefull to the health, such as antioxidant, anticancer and antibacterial. Biosynthesis of flavonoids in the plant is influenced by environmental factors, one of which is a nutrient that is nitrogen. This study aimed to determine the effect of nitrogen fertilizer on the content of flavonoids in Red amaranth leaves. The results of this study are expected to provide information to the public about the optimal nitrogen fertilizer to increase the levels of flavonoids in Red amaranth leaves. In this research, red amaranth seed planting with the addition of nitrogen fertilizers of different concentrations (0%, 2%, 4%, 6%, 8% and 10%) from week 1 through week 5. The leaves are harvested to extract and analyze the content of flavonoids. The parameters measured were the growth of a Red amaranth plant height, number of leaves and leaf width; and levels of flavonoids with aluminum chloride method. The results showed that nitrogen fertilizer application significantly increases the growth and flavonoids in Red amaranth.Keywords: red amaranth, nitrogen fertilizer, flavonoid.